DOP02 Increasing incidence of Inflammatory Bowel Disease in a high prevalence country: A nationwide study in Finland. (21st January 2022) - Kontola, K; Oksanen, P; Huhtala, H; Jussila, A T
Abstract: Background: The burden of inflammatory bowel disease (IBD) in health care is high and the incidence and prevalence rates of IBD in Finland are among the highest in the world. Our aim was to assess the actual incidence and the trends of IBD in Finland during 2000–2020 using nationwide registry-based data. We also estimated the nationwide prevalence of IBD in 2000 and 2020. Methods: This study included patients to whom IBD reimbursement was newly attributed between January 1, 2000 and December 31, 2021. Data were retrieved from the Social Insurance Institution of Finland. Incidence and prevalence rates were calculated by dividing the number of annual new IBD cases by the size of the population at risk during each calendar year. Results: A total of 42, 498 new IBD cases were identified during years 2000–2020; 31, 372 with ulcerative colitis (UC) and 11, 126 with Crohn's disease (CD).The crude annual incidence per 100, 000 increases in CD from 7.5 to 13.4 (IRR 1.02, CI 1.019 - 1.025) and in UC from 20.4 to 34.7 (IRR 1.03, CI 1.023 - 1.027) (Fig. 1). The crude prevalence of IBD increases from 376 to 972 per 100, 000 (PRR 1.05, CI 1.046–1.047).Men have significantly higher incidence than women in UC (IRR 1.26, CI 1.228–1.284). In contrast, there is no difference between genders among CD patients (IRR 0.98, CI 0.95–1.02). In UC, the peak incidence occurs in the age group 25–29 (Fig. 2), whereas in CD, the incidence is highest in slightly younger patients (Fig. 3). Figure 1. Incidence of ulcerative colitis and Crohn`s disease in Finland during 2000–2020 Figure 2. Annual incidence of UC by age groups during 2000–2020 Figure 3. Annual incidence of CD by age groups during 2000–2020 Conclusion: During the first two decades of the 21st century, the incidence of UC and CD continues to increase in Finland, and almost one percent of the population has IBD.